Modelo de negocio a través de la metodología canvas: instant food (2020)
In the following work, the idea of a virtual restaurant based on the canvas methodology will be developed, in order to explore the current needs and preferences of the consumer; in this way, two surveys will be carried out to know the judgment and opinion of their experience about nutrition and technology-based tools. The idea of developing a virtual restaurant model arises from the current boom in technology-based applications, the exponential growth of food sites that prepare food in unhealthy conditions and the poor nutrition that exists in products consumed daily.